PERLINDUNGAN HUKUM TERHADAP KORBAN TINDAK PIDANA PERDAGANGAN ORANG DAN MODUS REKRUTMEN KERJA LUAR NEGERI MELALUI MEDIA SOSIAL - Elenta Elenta; Rara Safira Haliza; Nadia Eliens Waruwu (Jurnal Ilmiah Multidisiplin Ilmu, 2026)
The crime of trafficking in persons (TPPO) with recruitment through social media is now a major problem in Indonesia, which exploits migrant workers in various online fraud operations. The Trafficking in Persons 2025 report recorded the handling of 3,354 cases related to online fraud in 2024, but only 314 individuals were officially recognized as victims. This upward trend is expected to continue in 2025–2026 with the mass repatriation of thousands of Indonesian citizens from Myanmar and Cambodia. This normative juridical research explores the inadequacy of legal protection contained in Law no. 21/2007, Law no. 18/2017, Law no. 31/2014, and the ITE Law. It was found that although the national legal system is quite complete, its implementation is hampered by low levels of digital literacy, weak responsibility of digital platforms, disharmonious coordination between sectors, and challenges in transnational electronic evidence. The low level of fulfillment of the right to restitution increasingly shows the state's failure to provide restorative justice. This research recommends the existence of special regulations regarding TPPO that focus on digital aspects and strengthening mechanisms.